CPU PERFORMANCE IMPROVEMENT AMD ATHLON THUNDERBIRD USINGOVERCLOCK - Hendra Gunawan; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Komputer, 2004)
Overclock is an activity "forcing", "spur", "optimize" a hardware such as processors, memory, display adapters, etc. for work outside the standard specifications limit its maker, because every manufacturer of hardware is always giving tolerance of labor value hardware products.That way, the technique is done properly overclock and neat, a discovery that would be quite beneficial for computer users as a free upgrade solution.